Membangun Brandmark Produk Rengginang UMKM Desa Karang Harum - Bernad Hananto; Wiranta; Iin Masriah; Suhrowardi; M Ulil Albab (JPPI: Jurnal Pengabdian Pelita Insani, 2024)
Karang Harum Village is one of the villages located in Kedungwaringin District, Bekasi Regency. In Karangharum Village, there are several home industries that process various raw products around their homes into processed products that have added value. One of the home industries that is still running today is the rengginang industry. The rengginang industry in this village is developing well and is still producing today. However, the absence of packaging and labeling makes this industry slightly hampered in terms of marketing. The method used in this community service activity is the method of mentoring and educating the community regarding marketing strategies, especially packaging and labeling. The final result of this study is packaging branding, labeling for rengginang processed products, and registration of the industry with the Health Service and the Industry, Trade, and Cooperatives Service, Bekasi Regency as a home industry based on processed agricultural products because the main ingredient is rice flour. Product labeling and registration of products with the relevant agencies are expected to spur and develop this industry on a wider scale.